Analisis Pemerolehan Bahasa pada Anak Usia 38 Bulan Berdasarkan Mean Longh of Utterance - Rizkiyatussalamiyah, Mudrikah; Setiawan, Hendra (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Language acquisition is a natural process where children acquire language without meaning to. Mean Length of Utterance (MLU) is used to measure language acquisition in a child's speech. MLU measures the average length of a child's utterances which reflects the language products produced. The aim of this research is to determine first language development in children aged 3 years 2 months. The research method used was descriptive qualitative with the subject being a child named Arabella. Data was collected through documentation techniques, namely recording and transcribing children's speech. The analysis results show that Arabella has 100 utterances with 210 morphemes. The MLU is 2.1 which means Arabella is in stage III for 27-28 months of age according to Brown's theory. Arabela's age should be at Stage VIII MLU. In terms of phonological acquisition, Arabella has mastered the pronunciation of vowels and some consonants well. However, some consonants such as /f/, /q/, /r/, /v/, /x/, and /z/ are still difficult for Arabella to pronounce.